Risk of breast cancer before and after rheumatoid arthritis, and the impact of hormonal factors. Issue 5 (11th March 2020) - Wadström, Hjalmar; Pettersson, Andreas; Smedby, Karin E; Askling, Johan
Abstract : Objectives: To examine the risk of incident breast cancer in women with rheumatoid arthritis (RA), and the risk of RA in women with a history of breast cancer, taking antihormonal treatment for breast cancer into account. Methods: Using nationwide Swedish registers, women with new-onset RA diagnosed in 2006–2016 were identified and analysed using a cohort and a case–control design. Each patient with RA was matched on age, sex and place of residence to five randomly selected subjects from the general population. Through register linkages, we collected information on breast cancer, breast cancer risk factors (reproductive history and hormone replacement therapy) and socio-economy. The relative risk of breast cancer after RA was assessed using Cox regression, and the relative risk of RA in women with a history of breast cancer was assessed using conditional logistic regression. Results: The risk of incident breast cancer in women with RA was reduced and the association was not attenuated by adjustment for breast cancer risk factors (HR=0.80, 95% CI 0.68 to 0.93). The risk of RA in women with a history of breast cancer was similarly reduced (OR=0.87, 95% CI 0.79 to 0.95). Women with breast cancer treated with tamoxifen (OR=0.86, 95% CI 0.62 to 1.20) or aromatase inhibitors (OR=0.97, 95% CI 0.69 to 1.37) did not have an increased risk of RA compared with women with breast cancer treated differently. Conclusions: The decreased occurrence of breast cancer in patients with RA is present already before RA diagnosis; these reduced risks are not readily explained by hormonal risk factors. Adjuvant antihormonal therapy for breast cancer does not seem to increase RA risk.